Study of Toll Road Procurement using Remote Sensing based on SNI No.13/P/BM/2021 - Rusgiyarto, Ferry; Kaffa, Niswah Selmi; Hadi, Sukanto; Iqbal, Muhammad; Putra, Moh. Nanang Lutfian (Jurnal Ilmiah Geomatika, 2025)
Road route planning requires a comprehensive study that considers various parameters. This can lead to time and cost inefficiencies. This study uses Geographic Information System (GIS) and remote sensing to analyze the procurement of a toll road from Jombang Regency to Malang City (Indonesia) based on SNI No. 13/P/BM/2021. The data used in this study are Sentinel-2 satellite imagery for land cover mapping, a Digital Elevation Model (DEM) for slope classification, and the Indonesian Topographic Map (RBI) as the mapping basemap. The land cover mapping was performed using NDVI, NDBI, and NDWI algorithms using bands 2, 3, 4, 8, and 11 from Sentinel-2 2A imagery validated by ground truth data. The alternative routes were generated, each based on a different overlay configuration regarding slope and landcover aspects. The weight configuration was determined using the Analytical Hierarchy Process (AHP). The results of the process indicate that the most effective overlay configuration is 0.75 for land cover and 0.25 for slope. Based on the overlay results, route 3 emerged as the most optimal route with a total length of 47.75 km. On route 3, only one station (STA) is located on a slope with a gradient of more than 50%, which mostly crosses open land and vegetation areas, with only three STAs located within the built-up areas. This route does not require bridges, thus offering the potential for reducing land acquisition costs.